Anti-VEGF Cancer Therapy in Nephrology Practice - Hassan Izzedine (International Journal of Nephrology)
Expanded clinical experience with the antivascular endothelial growth factor (VEGF) agents has come with increasing recognition of their renal adverse effects. Although renal histology is rarely sought in antiangiogenic-treated cancer patients, kidney damage related to anti-VEGF is now established. Its manifestations include hypertension, proteinuria, and mainly glomerular thrombotic microangiopathy. Then, in nephrology practice, should we continue to perform kidney biopsy, and what should be done with the anti-VEGF agents in case of renal toxicity?